Sentiment Analysis on Prabowo Subianto Using Naive Bayes on Twitter - Toteng, Benediktus Rivaldi; Asriningtias, Yuli (Kirana Publisher (KNPub), 2025)
General elections are a mechanism to implement the sovereignty of the people with the aim of creating a democratic state government based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Elections are held every five years and involve the election of the President and Vice President, Members of the People's Representative Council, Regional Representative Council, Regional People's Representative Council, as well as regional heads and deputy regional heads. Elections aim to select leaders who can reflect democratic values and represent the aspirations of the people in accordance with the life of the nation and state. To understand public opinion regarding the 2024 elections, a sentiment analysis was conducted. This sentiment analysis aims to determine the public's positive and negative responses towards Presidential Candidate Prabowo Subianto. Sentiment Analysis of Prabowo Subianto Using Naive Bayes On Twitter, data was collected from the social media platform using the hashtag, #Prabowo.